2022
DOI: 10.1002/slct.202200077
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Novel Triazolothiadiazine‐Coumarins Catalyzed by Agro Waste Extract: An Approach towards In‐Silico and In‐Vitro Anti‐Fungal Activity

Abstract: A green, commodious, immensely versatile synthetic route for agro waste extract WELPSA catalyzed cyclocondensation of biologically active triazolothiadiazine‐coumarin hybrid derivatives has been studied. A proficient synthesis offused heterocycles 9 i–wvia dehydrative condensation with cyclization of4‐((4‐amino‐5‐mercapto‐4H‐1,2,4‐triazol‐3‐yl)methyl)‐2‐aryl‐2,4‐dihydro‐3H‐1,2,4‐triazol‐3‐one (5 a‐‐c) and substituted bromoacyl coumarins (8 d‐‐h)has been incorporated in presence of different catalysts including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…IC 50 values of 10–50, 50–100, and >100 μg mL −1 signify strong, moderate and poor antioxidant activities respectively. 34 The results of the accomplished radical scavenging activity, shown in Table 4, demonstrated that the compounds 8f , 8h , 8i , 8l , 8n , 8p , 8r , 8s , and 8t with substituents such as halogen, alkyl and amine groups demonstrated very good antioxidant activities with IC 50 values of 24.12, 23.04, 24.25, 20.45, 21.39, 22.89, 24.26, 24.36 and 21.85 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…IC 50 values of 10–50, 50–100, and >100 μg mL −1 signify strong, moderate and poor antioxidant activities respectively. 34 The results of the accomplished radical scavenging activity, shown in Table 4, demonstrated that the compounds 8f , 8h , 8i , 8l , 8n , 8p , 8r , 8s , and 8t with substituents such as halogen, alkyl and amine groups demonstrated very good antioxidant activities with IC 50 values of 24.12, 23.04, 24.25, 20.45, 21.39, 22.89, 24.26, 24.36 and 21.85 (Fig. 3).…”
Section: Resultsmentioning
confidence: 99%
“…Imidazo[2,1‐ b ]thiazole being one such medicinally vital synthetic product is one of the most important fused sulfur‐containing heterocycles widely found in the various biologically active agents (Figure 1). [ 1–4 ] Renowned anthelmintic and immunomodulatory drug Levamisole marketed under the trade name Ergamisol composes of imidazo[2,1‐ b ]thiazole system as its fundamental unit. [ 5,6 ]…”
Section: Introductionmentioning
confidence: 99%
“…Imidazo [2,1-b]thiazole being one such medicinally vital synthetic product is one of the most important fused sulfur-containing heterocycles widely found in the various biologically active agents (Figure 1). [1][2][3][4] Renowned anthelmintic and immunomodulatory drug Levamisole marketed under the trade name Ergamisol composes of imidazo [2,1-b]thiazole system as its fundamental unit. [5,6] The establishment of C-N bonds is a persisting topic owing to the immense efficacy of nitrogen-comprising compounds in various natural products, bioactive molecules, and pharmaceutical drugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations